(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This paper examines the causes of arrhythmia, which are divided into four groups. It is shown that one of the most striking examples of rhythm disturbances is caused by an imbalance between the sympathetic and parasympathetic branches of the autonomic nervous system. Changes in the normal automaticity of the heart lead to the development of sinus arrhythmias.